PENGARUH KEGIATAN EKSTRAKURIKULER PUBLIC SPEAKING TERHADAP KARAKTER KOMUNIKATIF PESERTA DIDIK DI MI DARUL FIKRI PONOROGO JAWA TIMUR INDONESIA - Fatimatul ‘Aliyah; Katni Katni; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to determine the effect of extracurricular public speaking activities on the communicative character of class IV-VI students of MI Darul Fikri. This type of research is quantitative research, test analysis, data collection methods using questionnaires, observation, and documentation. The total population of 133 students consists of 7 classrooms. The sample of this research was taken using the formula Slovin, which was obtained as many as 57 of the 133 students. Hypothesis testing includes 2 stages, namely the product-moment correlation test and simple linear regression test using the SPSS 20 application. The results of this study can be concluded that three is a significant effect of extracurricular public speaking activities on the communicative character of class IV-VI students of MI Darul Fikri Bringin Kauman Ponorogo. This is evidenced by the amount of 0.258 or 25.8% while 74.2% is influenced by other factors